Evaluation of Some Selected the Minerals and Vitamins Contents and Partial Oil Characterization of African Oil Bean (Pentaclethra macrophylla Benth) Seed - (:unkn) unknown (My University, 2025)
Background and Objective: The African oil bean (Pentaclethra macrophylla) is a specie of the family Leguminosea and an indigenous of tropical Africa. The seed is widely consumed by Nigerians especially in Eastern part of Nigeria. It can be used as flavoring in food and also serves as a substitute for meat. This research work is aimed at evaluating the nutritional constituents of the African oil bean (Pentaclethra macrophylla) seed. Materials and Method: The African oil bean seed was evaluated for vitamin, minerals and partial oil characterization using standard Spectroscopic methods. Results: The results gotten from the evaluation of vitamins A, D, C, E and Folate were; 9.32%, 19.34%, 68.83%, 37.60% and 0.25% respectively and this shows that the seed is rich in vitamin C. The mineral analysis for Se, Co, Cu, Ca, Zn, Mn, Fe, Mg, K and Na were; 0.077%, 0.045%, 0.395%, 8.484%, 0.430%, 0.172%, 2.199%, 5.747%, 5.270% and 5.923% respectively and the result shows that the African oil bean seed is a rich source of calcium. The oil characterization analysis for saponification value, peroxide value, iodine value, acid value and free fatty acid value were; 134.64%, 12.5%, 89.93%, 7,641% and 3.821% respectively. The high iodine value of the seed oil shows that it cannot be classified as a non-drying oil and cannot be used for paint or polish production. However, the low free fatty acid value shows the oil is edible. The low saponification value shows that the oil contains low molecular weight fatty acid glyceride. Conclusion: The seed has proven to be beneficial, not only as a food source but also a therapeutic agent for combating diseases.
Keywords: African Research